2017
DOI: 10.1007/s11325-017-1494-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing and managing sleep apnea in patients with chronic cerebrovascular disease: a randomized trial of a home-based strategy

Abstract: BackgroundObstructive sleep apnea is common and associated with poor outcomes after stroke or transient ischemic attack (TIA). We sought to determine whether the intervention strategy improved sleep apnea detection, obstructive sleep apnea (OSA) treatment, and hypertension control among patients with chronic cerebrovascular disease and hypertension.MethodsIn this randomized controlled strategy trial intervention, patients received unattended polysomnography at baseline, and patients with OSA (apnea-hypopnea in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…These differences may be due to the lower AHI cut-off (≥5 vs. >10 /hour) and the exclusion of those who received thrombolysis from other similar studies (20). This study confirms previous study findings of a very high level of undiagnosed sleep apnea (4.4% prior diagnosis of OSA) within the community (21). While the onset of OSA may be de novo post stroke most of the evidence suggests that it usually is a pre-existing condition (5).…”
supporting
confidence: 87%
“…These differences may be due to the lower AHI cut-off (≥5 vs. >10 /hour) and the exclusion of those who received thrombolysis from other similar studies (20). This study confirms previous study findings of a very high level of undiagnosed sleep apnea (4.4% prior diagnosis of OSA) within the community (21). While the onset of OSA may be de novo post stroke most of the evidence suggests that it usually is a pre-existing condition (5).…”
supporting
confidence: 87%
“…Most studies have suggested beneficial effects, particularly in sleepiness, depression, functional recovery, and recurrent events [69][70][71][72]. A home-based randomized trial on managing sleep apnea in chronic stroke patients showed that CPAP use at home improved OSA symptoms compared with non-use (Table 2) [73]. Two randomized controlled studies also proved that CPAP was superior to conventional therapies in terms of neurological recovery [74,75].…”
Section: Treatment Of Bsds In Strokementioning
confidence: 99%
“…CSA and Cheyne–Stokes respiration (CSR) are common in patients with heart failure and may be seen following ischaemic or haemorrhagic stroke, although the prevalence is significantly less than that seen in heart failure . Sleep fragmentation arising from arousals following apnoeic events likely contribute to fatigue and sleepiness reported by patients.…”
Section: Adaptive Servoventilationmentioning
confidence: 99%
“…CSA and Cheyne-Stokes respiration (CSR) are common in patients with heart failure 28 and may be seen following ischaemic or haemorrhagic stroke, although the prevalence is significantly less than that seen in heart failure. 29,30 Sleep fragmentation arising from arousals following apnoeic events likely contribute to fatigue and sleepiness reported by patients. Furthermore, repetitive apnoeas and arousals induce an increase in sympathetic nerve activity, which is associated with adverse physiological effects and poorer prognosis in patients with chronic heart failure (CHF).…”
Section: Cheyne-stokes Breathingmentioning
confidence: 99%